Urban planning for multiethnic city sustainability - Emília Maria Delgado Domingos Antunes Malcata Rebelo (2004)
The main purpose of this paper is to report the main results and conclusions of a research project currently being lead at the Urban, Territorial and Environment Planning Section at The Faculty of Engineering of Oporto University (Portugal). It basically consists in the research of how Territorial and Urban Planning (for different planning levels and implementation processes) supports an effective territorial, urban, social, economic, cultural and sociological integration of immigrant people and ethnic minorities, in what concerns spatial distribution and features of their dwellings and jobs. Sustainability is here apprehended in a long-range planning perspective, taking special care about the relationships between different ethnic minorities' features, and physical location and characteristics of jobs, and physical location and characteristics of ethnic minorities' groups dwellings and their neighborhoods. The research focuses on the importance of the Planning for Ethnic Minorities' sustained development and integration, reflecting about the institutional framework and co-ordination, public participation and involvement, and monitoring of some urban indicators behavior. Sustained development is faced as the ability of the urban area and its region to continue to function at levels of quality of life desired by the community, satisfying the current societal needs, without restricting the options available to the present and future generations, and without causing adverse impacts inside and outside the urban boundary (Brundtland Report, World Commission on Environment and Development, 1987). The main issues to be examined thoroughly related to: - The relations between employment/unemployment, the race/ethnic group, and the spatial dwelling location (and respective neighborhood features) and job location (and respective features). - Barriers faced by ethnic minorities in what concerns dwelling access, in theoretical, social and geographical terms in certain urban areas.- Relation between the kind of dwelling ownership, the dwelling features, their spatial location/distribution, and the socio-economic-cultural features of each ethnic group. - Assessments of the way the spatial, social and cultural location of ethnic minorities affect the supply and demand patterns of dwellings. - Evaluation of the political and social implications of social housing reallocation to specific community groups of ethnical minorities. As a main output of the research, a neural network model is developed aimed to support municipal power decisions in what concerns planning for sustainability related to ethnic minorities economic, social, cultural and ecological integration. Simulations of alternative urban policies are performed through this model (corresponding to different hypothetical combinations of different variables), and the potential results are displayed in cartographic terms through a geographic information system cartographic interface. The results of this research project are evaluated in terms of a set of urban policies and "best practices" proposed in order to enhance overall urban sustainability. This model, and the respected interface are developed and applied to the Oporto city (Portugal), but the methodology and results can be easily extrapolated to other urban realities.